2022
DOI: 10.54099/hbr.v2i2.100
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Organisasi dan Kinerja Karyawan

Abstract: Systematic literature review ini bertujuan untuk mensintesis beberapa penelitian yang berkaitan dengan pengaruh budaya organisasi terhadap kinerja karyawan. Penelitian ini disusun menggunakan Prefered Reporting Item for Systematic Review and Meta Analysis dari penelitiaan yang memiliki kaitan dengan pengaruh budaya organisasi terhadap kinerja karyawan. Metode pengumpulan data menggunakan metode Popuation, Intervention, Comparison, and Outcome dengan menggunakan 2 akses yaitu Google Cendikia dan Garba Rujukan D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The findings of this study are in line with several previous studies that have identified a relationship between organizational culture and employee job satisfaction. Previous research has also shown that a positive and inclusive organizational culture can improve job satisfaction, motivation, and employee performance (Kontoghiorghes, 2016;Tamimi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are in line with several previous studies that have identified a relationship between organizational culture and employee job satisfaction. Previous research has also shown that a positive and inclusive organizational culture can improve job satisfaction, motivation, and employee performance (Kontoghiorghes, 2016;Tamimi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It includes the norms, values, beliefs, and behaviors within an organization, reflecting its identity, goals, and ways of operating (Chatman & O'Reilly, 2016). According to Tamimi et al (2022), the formation, development, strengthening, or change in organizational culture requires practices that unite members' cultural values with the organization's cultural values. The definition of organizational culture is norms, values, presumptions, beliefs, philosophy, organizational habits, and other things that are created over an extended period of time by the organization's founders, leaders, and members; these things are then instilled in new members and used in the production of goods, the provision of customer service, and the accomplishment of organizational objectives (Jamal et al, 2022;Firdaus & Idris, 2023).…”
Section: Figure 1 Vehicle Insurance Premiumsmentioning
confidence: 99%
“…The rationale behind selecting VOSviewer lies in its capacity to handle large datasets and offer a range of visually appealing and informative outputs, including Co-Authorship, Co-Accurrence, and Citation maps based on shared citations in the network (Nur et al, 2020). This study adheres to specific criteria for determining article methods up to the year of publication of citations, a methodology further scrutinized (Tamimi et al, 2022). The study follows a five-stage method borrowed from previous research findings (Setyaningsih et al, 2018), as depicted in Figure 3 below.…”
Section: Figure 2 Exploration Approachmentioning
confidence: 99%